Valencene synthase from the heartwood of Nootka cypress (Callitropsis nootkatensis) for biotechnological production of valencene. Issue 2 (25th September 2013) - Beekwilder, Jules; van, Adèle; Cankar, Katarina; van, Aalt D.J.; de, René M.; Stoopen, Geert; Bouwmeester, Harro; Achkar, Jihane; Sonke, Theo; Bosch, Dirk
Summary Nootkatone is one of the major terpenes in the heartwood of the Nootka cypress Callitropsis nootkatensis. It is an oxidized sesquiterpene, which has been postulated to be derived from valencene. Both valencene and nootkatone are used for flavouring citrus beverages and are considered among the most valuable terpenes used at commercial scale. Functional evaluation of putative terpene synthase genes sourced by large‐scale EST sequencing from Nootka cypress wood revealed a valencene synthase gene (CnVS). CnVS expression in different tissues from the tree correlates well with nootkatone content, suggesting that CnVS represents the first dedicated gene in the nootkatone biosynthetic pathway in C. nootkatensis The gene belongs to the gymnosperm‐specific TPS‐d subfamily of terpenes synthases and its protein sequence has low similarity to known citrus valencene synthases. In vitro, CnVS displays high robustness under different pH and temperature regimes, potentially beneficial properties for application in different host and physiological conditions. Biotechnological production of sesquiterpenes has been shown to be feasible, but productivity of microbial strains expressing valencene synthase from Citrus is low, indicating that optimization of valencene synthase activity is needed. Indeed, expression of CnVS in Saccharomyces cerevisiae indicated potential for higher yields. In an optimized Rhodobacter sphaeroides strain, expression of CnVS increased valencene yields 14‐fold to 352 mg/L, bringing production to levels with industrial potential.